Auditoria e o impacto nas organizações - Guedes, Ana Cristina Pinto Cal (2022)
The purpose of this dissertation is to understand what conditions organizations in carrying out audits. The legislation requires it in certain circumstances, however some companies, in which there is no obligation, choose to do it because of the advantages. It is also intended to understand the opinion of the auditors on the subject and how they are prepared to adapt their services to the needs of the market. To undertake this investigation, a theoretical exposition of the subject was carried out, analyzing previous studies and the analysis of surveys to organizations in order to understand the impact that the performance of an audit has on companies and if they recognize the added value that can result from it. This study also comprises a questionnaire with open questions for auditors to understand the perception that companies have in relation to auditing, auditing in general and its evolution. In general, the results suggest that audits have a positive and fundamental role as they add value to organizations, improving the efficiency of processes and helping to maintain their presence in the market. They guide entities and enable the prevention and detection of errors and fraud, contributing to the maintenance of a good reputation. Auditors understand the needs of the market and intend to adapt to its needs, but they need a deep change and investments in technology so that the practice of the profession could be faster.